Canola oil/candelilla wax oleogel improves texture, retards staling and reduces in vitro starch digestibility of maize tortillas. (2nd December 2019) - Vernon‐Carter, Eduardo Jaime; Alvarez‐Ramirez, Jose; Meraz, Monica; Bello‐Perez, Luis Arturo; Garcia‐Diaz, Samuel
Abstract: BACKGROUND: Maize tortilla staling is a major drawback that affects its commercialization and consumption, and so novel methods for retarding staling are continuously being explored. The present study evaluated the effect of adding a canola oil/candelilla wax oleogel (CWO; 0. 2, 4 and 6 g 100 g −1 ) to a basic masa formulation (water, 60 g 100 g −1 ; nixtamalized maize flour, 40 g 100 g −1 ) on the texture, staling and in vitro starch digestibility of maize tortillas made using a hot plate (200 °C). RESULTS: Textural analysis showed that CWO reduced hardness and increased the tensile strength of tortillas. Fourier transform infrared analysis indicated that the retrogradation of starch chains, quantified in terms of the intensity ratio 1047/1022, was reduced by oleogel incorporation. In vitro starch digestibility tests showed that tortillas containing CWO had lower readily digestible and slowly digestible starch fractions compared to the control tortilla without oleogel. CONCLUSION: The formation of amylose–lipid inclusion complexes and the formation of an oily physical barrier around starch granules were postulated as mechanisms underlying the reduced starch digestibility. © 2019 Society of Chemical Industry